Charcot's son, commander Jean-Baptiste Charcot: from neurology to "Pourquoi Pas?" - Hélio A. G. Teive; Renato P. Munhoz; Jefferson C. Simões (Arquivos de Neuro-Psiquiatria)
Charcot name became very famous around the world, firstly because of the work of Professor Jean-Martin Charcot, the founder of Clinical Neurology, and, secondly, because of his son, Jean-Baptiste, the world famous maritime explorer.